Maximizing confidence in a negative result: Quantitative sample adequacy control - Ivan Brukner; Shaun Eintracht; Andreas I. Papadakis; David Faucher; Bruno Lamontagne; Alan Spatz; Matthew Oughton (Elsevier, 2020)
Quantitative PCR (qPCR) is a leading screening tool, permitting rapid detection of pathogens and the maintenance of effective infection control programs. Unfortunately, qPCR assays frequently do not incorporate Sample Adequacy Control (SAC). A SAC controls for the quantity, quality and adequacy of the specimen. Without SAC, the confidence in a negative result remains questionable and the efficacy of screening is compromised. Ultimately, the exclusion of SAC from qPCR may result in false negative results. One should consider SAC to be an integral critical type of laboratory control; addressing diverse analytical problems, such as sample adequacy, sample processing and assay inhibition. Following distribution of cycle threshold values (Cq) of Influenza A positive results and Cq values of SAC, obtained from nasopharyngeal swabs, we showed that the confidence in a negative result cannot be guaranteed in the presence of a weak positive SAC signal (late Cq values). Herein, we explain why widespread inclusion of sample adequacy control in routine screening is blocked. A protocol and methods for SAC threshold establishment are offered.